2020
DOI: 10.1590/1806-93042020000200002
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness on health education to prevent nipple trauma from breastfeeding: a systematic review

Abstract: Objectives: to analyze the effectiveness on health education to prevent nipple trauma in breastfeeding compared to other interventions. Methods: systematic literature review was carried out in January 2019, according to PRISMA recommendations. The searches were conducted in Cinahl, PubMed, Web of Science, Scopus, and in the references cited in the selected articles. The studies were assessed for quality and level of evidence according to the Grading of Recommendations, Assessment, Development, and Evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
4
Order By: Relevance
“…Uma observação importante é que, todas as intervenções foram conduzidas no pós-parto, o que aponta para a necessidade de pesquisas clínicas sobre a prevenção de lesões mamilo-areolares no pré-natal. (27) Sobre o tratamento tópico, há uma ampla variedade de condutas e produtos apresentados na literatura, mas o consenso entre todas é a manutenção da umidade na área mamiloareolar. (28) A combinação do tratamento tópico, com estratégias de educação em saúde, potencializam o efeito positivo da intervenção, bem como a utilização de materiais que auxiliassem na redução do contato da lesão com a vestimenta, também favoreceram a cicatrização.…”
Section: Discussionunclassified
“…Uma observação importante é que, todas as intervenções foram conduzidas no pós-parto, o que aponta para a necessidade de pesquisas clínicas sobre a prevenção de lesões mamilo-areolares no pré-natal. (27) Sobre o tratamento tópico, há uma ampla variedade de condutas e produtos apresentados na literatura, mas o consenso entre todas é a manutenção da umidade na área mamiloareolar. (28) A combinação do tratamento tópico, com estratégias de educação em saúde, potencializam o efeito positivo da intervenção, bem como a utilização de materiais que auxiliassem na redução do contato da lesão com a vestimenta, também favoreceram a cicatrização.…”
Section: Discussionunclassified
“…Mesmo com sete ou mais consultas, 22 mães apresentaram lesão mamilo-areolar. (7) A educação na amamentação, com foco na técnica adequada, deve ser realizada rotineiramente no pré-natal e no pós-parto, desde a primeira mamada, (33) reforçando a orientação às lactantes acerca da amamentação e de formas de tratar e evitar o surgimento das lesões. (7) Orientações sobre a pega e posicionamento corretos se mostram como fatores protetivos ao trauma mamilar.…”
Section: Discussionunclassified
“…In order to initiate breastfeeding successfully, breast examination should be performed and breastfeeding education should be given, especially in the last trimester (Oliveira et al, 2020). It is emphasized that the role of midwives/nurses is crucial in breastfeeding education to give support in antenatal, maternity, and postpartum period (Swerts et al, 2016).…”
Section: Covid-19 and Lactation Counselingmentioning
confidence: 99%
“…In a systematic review, it was reported that supporting breastfeeding and providing breastfeeding education play a key role in preventing breastfeeding problems (Oliveira et al, 2020). It is important to WHO, 2016).…”
Section: Covid-19 and Lactation Counselingmentioning
confidence: 99%